In vitro ochratoxin A adsorption by commercial yeast cell walls - Pereyra, Carina Maricel (2015)
The aim of the present study was to evaluate the ochratoxin A (OTA) adsorption capacity by two kinds of commercial yeast cell walls (YCW1 and YCW2) used as dietary supplements. An in vitro test was designed to mimic the temperature (37ºC), pH (2) and passage time (30 min) through the stomach of a monogastric animal. The test was performed using different concentrations of YWC (100 and 200 µg/mL) and OTA (10; 80; 160 and 1000 ng/mL) and extracts were quantified by HPLC. For each OTA concentration, two independent trials varying the concentration of each YCW were performed. The two YCW assayed containing different percentages of polysaccharides, were able to adsorb similar amounts of OTA. Furthermore, the relationship mannans/β-glucans does not influence the rate of adsorption of OTA. In general, it was observed that the adsorption capacity increased with decreasing OTA concentration. Results from this work related to adsorption capacity of OTA with YCW allow predicting that other factor than 3D-structure and β-glucans and mannans could be involved. Future studies could be conducted to test the in vivo binding ability to alleviate the toxic effects of OTA under field conditions. Both YCW are a promising mycotoxin adsorbent to be used in animal feed to prevent mycotoxicoses.